International Trade in Manufactured Products : A Ricardo-Heckscher-Ohlin Explanation with Monopolistic Competition - Choudhri, Ehsan (IMF Working Papers; Working Paper ;, 2001)
A large data set on trade in manufactured products is used to evaluate the performance of a model that combines both the Ricardian and Heckscher-Ohlin effects and incorporates monopolistic competition. The paper estimates a relation implied by the model to explain relative sectoral exports of major countries to a number of important markets, using 1970-90 data for nine manufacturing sectors. The relation fits the data well and variables suggested by both traditional and new trade models play an important role in explaining relative exports.